Phaseolus costaricensis, a new wild bean species (Phaseolinae, leguminosae) from Costa Rica and Panama, Central America - Freytag, George F.; Debouck, Daniel G. (JSTOR, 1996)
During a review of Phaseolus under-taken by the senior author to clarify the variability of the P. coccineus L. species complex, a few herbarium specimens of what appeared to be a new species from Costa Rica and Panama were encountered. Subsequent field collecting by the junior author confirmed this opinion, and the new taxon is hereby named and described. Its probable relationships and the part it may have played in the early evolution of the economically important pulses such as the common bean, scarlet runner bean, and "polyanthus" bean are discussed. As a result of an in-depth review of the genus Phaseolus, originally begun by the senior author to clarify the variability of the P. coccineus L. species complex, and the fieldwork subsequently carried out by the junior author (Debouck et al., 1989), a large vining wild bean growing in the montane forests of Costa Rica appears to be new to science. As described and discussed below, it shares many morphological traits with wild P. vulgaris L. and wild P. dumosus Macfadyen (= P. polyanthus Greenman; see Schmit & Debouck, 1991, for discussion) and will therefore be grouped with these two species to form the section Phaseolus in a monograph currently in preparation